Leadership Effect and Work Environment on Employee Performance With Motivation Variables as Mediation (Study at The Wangsa Hotel) - I Kadek Kertiyasa (JUSTBEST: Journal of Sustainable Business and Management, 2021)
This study aims to analyze the influence of leadership and work environment on employee performance with motivational variables as a mediation at The Wangsa Hotel. The research was conducted at The Wangsa Hotel. The number of respondents were 60 people. The sampling technique used in this study was saturated samples. Data retrieval is done by questionnaire with Likert scale. The method of analysis uses descriptive analysis and inferential analysis. The results of the analysis showed that leadership does not affect motivation, meaning that leadership has not been able to increase employee motivation at the The Wangsa hotel. The work environment has a positive and significant influence on motivation, it means that the increasing work environment, the work motivation of employees increases. Leadership has a positive and significant effect on employee performance, it means that the better the leadership, the employee's performance increases. The work environment does not affect employee performance, it means that the work environment has not been able to influence the performance of the hotel employees of The Wangsa. Motivation has a negative and significant influence on employee performance, it means that the higher the motivation, the performance will decrease.